Architecture and Dynamics of the Wounding-Induced Gene Regulatory Network During the Oolong Tea Manufacturing Process (Camellia sinensis) - Zheng, Yucheng; Hu, Qingcai; Yang, Yun; Wu, Zongjie; Wu, Liangyu; Wang, Pengjie; Deng, Huili; Ye, Naixing; Sun, Yun (Frontiers in Plant Science, 2022)
Understanding extensive transcriptional reprogramming events mediated by wounding during the oolong tea manufacturing process is essential for improving oolong tea quality. To improve our comprehension of the architecture of the wounding-induced gene regulatory network, we systematically analysed the high-resolution transcriptomic and metabolomic data from wounding-treated (after turnover stage) tea leaves at 11 time points over a 220-minute period. The results indicated that wounding activates a burst of transcriptional activity within 10 minutes and that the temporal expression patterns over time could be partitioned into 18 specific clusters with distinct biological processes. The transcription factor (TF) activity linked to the TF binding motif participated in specific biological processes within different clusters. A chronological model of the wounding-induced gene regulatory network provides insight into the dynamic transcriptional regulation event after wounding treatment (the turnover stage). Time series data of wounding-induced volatiles reveal the scientific significance of resting for a while after wounding treatment during the actual manufacturing process of oolong tea. Integrating information-rich expression data with information on volatiles allowed us to identify many high-confidence TFs participating in aroma formation regulation after wounding treatment by using weighted correlation network analysis (WGCNA). Collectively, our research revealed the complexity of the wounding-induced gene regulatory network and described wounding-mediated dynamic transcriptional reprogramming events, serving as a valuable theoretical basis for the quality formation of oolong tea during the postharvest manufacturing process.